Pantera: A PIC-MCC-DSMC software for the simulation of rarefied gases and plasmas - P. Parodi; S. Boccelli; F. Bariselli; T.E. Magin (SoftwareX, 2025)
We present Pantera, an open-source, parallel, particle-based code for the simulation of rarefied gases and plasmas. The code uses the Particle-in-Cell (PIC) method for the solution of ionized flows in the electrostatic approximation, coupled to the Direct Simulation Monte Carlo (DSMC) method for particle–particle interactions, and Monte Carlo Collisions (MCC) technique for the interaction of particles with a fixed background. It uses unstructured grids, which allows for the representation of complex geometries. Various models are available for elastic collisions, reactions, and gas–surface interaction. Semi- and fully-implicit, energy-conserving PIC schemes are available, as well as a Boltzmann-fluid model for electrons, to improve numerical stability and speed up the simulations. The code is designed to be easily understandable and extensible to include new models and algorithms for aerospace applications and beyond.